The Effect of Different Circadian Blood Pressure Rhythms on Left Ventricular Systolic Dyssynchrony in Patients with Newly Diagnosed Essential Hypertension. Issue 1 (27th July 2013) - Turak, Osman; Özcan, Firat; Kadife, İskender and İşleyen, Ahmet and Cebeci, Muhammet and Başar, Fatma Nurcan and Selçuk, Mehmet Timur and Gölbaşi, Zehra and Aras, Dursun and Aydoğdu, Sinan
<x xml:space="preserve">Abstract</x> Objectives Left ventricular (LV) synchronous contraction is impaired in patients with hypertension (HT). The deleterious effects of HT on cardiovascular system are more evident in patients with nondipper HT than dippers. In this study, we aimed to investigate the effect of nondipping HT on LV systolic synchronicity compared with dippers and controls. Methods One hundred patients with newly diagnosed essential HT and 50 normotensive subjects were enrolled in this study. The hypertensive patients were assigned 2 groups comprising 55 dippers and 45 nondippers. Each subject underwent a comprehensive transthoracic echocardiographic examination. The evaluation of systolic dyssynchrony was performed by tissue synchronization imaging, and the time to regional peak systolic tissue velocity (Ts) in LV was measured on the basis of 12 segmental models. The standard deviation (SD) of the 12 LV segments (Ts‐SD‐12) and maximal difference in Ts between any two of the 12 LV segments (Ts‐12) were calculated. Results Compared with the control group, the synchronicity indexes were significantly prolonged in the hypertensive patients. Furthermore, Ts‐SD‐12 and Ts‐12 values were found to be significantly impaired in patients with nondipper HT, compared with dippers: Ts‐SD‐12 (38.1 ± 18.7 vs. 31.8 ± 15.4, P ≤ 0.001); Ts‐12 (123.0 ± 50.6 vs. 98.4 ± 42.3, P ≤ 0.001). Stepwise multivariate logistic regression analysis revealed a significant negative association between LV dyssynchrony indices and percentage decline in BP level from day to night. Conclusion Synchronous systolic contraction of LV is found to be significantly impaired in patients with nondipping circadian pattern of HT compared with dippers and the controls.